Independent Curriculum Analysis from Constructivism and Ki Hajar Dewantara Philosophy Perspective - Walad, Muzakkir; Suastra, Wayan; Nasri, Ulyan; Manap, Abdul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research discusses the central role of education in reform in Indonesia through the Independent Curriculum, with a constructivist philosophical approach and Ki Hajar Dewantara's perspective. This literature research aims to explain the Independent Curriculum from the perspective of constructivism and the philosophy of Ki Hajar Dewantara. This research aims to understand the extent to which the Merdeka Curriculum implements a constructivist approach and to determine the implementation of character education values and the formation of national identity in the Merdeka Curriculum by the views of Ki Hajar Dewantara. The results of this research show that the Merdeka Curriculum perspective from constructivism and Ki Hajar Dewantara's philosophy shows the importance of active student participation, social interaction, learning contextuality, character values, national identity, local wisdom, freedom and student independence. Holistic evaluation is needed to ensure implementation that is consistent with the philosophical vision, thereby creating individuals with character, national identity and independence.